1965
DOI: 10.1042/bj0970579
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the structure of bacilysin

Abstract: 1. Elementary analysis and other properties of a highly purified preparation of bacilysin indicated that a possible molecular formula for the substance is C(12)H(18)N(2)O(5). The results of electrometric titration were consistent with the hypothesis that the substance was a peptide containing one free alpha-amino group and one free carboxyl group. 2. Hydrolysis of bacilysin with 6n-hydrochloric acid at 105 degrees yielded l-alanine and l-tyrosine, but the ultraviolet spectrum of the substance showed that no ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…The evidence for the presence of a thiol group in the glucosamine synthase together with the known reaction of the thiol group of cysteine with the epoxide group in the anticapsin moiety of bacilysin (Rogers et al, 1965) suggested that the irreversible inhibition of the enzyme by anticapsin was a consequence of the formation of a covalent bond when the epoxide group for the latter was attacked by the thiol group of a cysteine residue in the enzyme.…”
Section: Purijication and Properties Of Glucosamine Synthasementioning
confidence: 99%
“…The evidence for the presence of a thiol group in the glucosamine synthase together with the known reaction of the thiol group of cysteine with the epoxide group in the anticapsin moiety of bacilysin (Rogers et al, 1965) suggested that the irreversible inhibition of the enzyme by anticapsin was a consequence of the formation of a covalent bond when the epoxide group for the latter was attacked by the thiol group of a cysteine residue in the enzyme.…”
Section: Purijication and Properties Of Glucosamine Synthasementioning
confidence: 99%
“…First, the inhibitory activity against grampositive and gram-negative bacteria was inactivated only by pronase E, which is the only protease that inactivates bacilysin (10,11). Second, the inhibitory activity against E. coli was reversed by the addition of N-acetylglucosamine, a known competitive inhibitor of the activity of bacilysin (5).…”
Section: Fig 2 Disk Assay Of Preparative C 18 Hplc Fractions Frommentioning
confidence: 99%
“…The molecule was described as C 12 H 18 N 2 O 5 with a molecular weight of 270 Da. Its hydrolysis by means of acid treatment yielded l-alanine and an uncharacterized L-amino acid like a tyrosine derivative [10]. Walker and Abraham isolated bacilysin and its terminal epoxy amino acid in improved yields from the culture fluids and by the application of physicochemical methods, assigned its exact chemical structure as L-alanyl-b-(2,3-epoxycyclohexanonyl)-L-alanine [11,12].…”
mentioning
confidence: 99%